Exploring Students' Perception on Using TikTok Account @kampunginggrislccom for Learning Vocabulary - Cici Situmorang; Nuril Nafisah; Siti Annisa; Siti Fatimah Az-zahra (Journal of Innovative and Creativity, 2026)
This research seeks to explore how students view the implementation of the TikTok account @kampunginggrislccom as a tool for enhancing their English vocabulary skills. A descriptive quantitative approach was utilized, which involved handing out a questionnaire to participants from the English Education Study Program at Institut Prima Bangsa Cirebon. The questionnaire included ten statements measured on a five-point Likert scale. Data gathered from the survey were processed using Microsoft Excel, where mean scores and percentages for each statement were computed. Findings reveal that students mainly hold a favorable view of using TikTok as an educational resource. Most respondents agreed that the video content is clear, visually appealing, and helpful in understanding English vocabulary. Therefore, the TikTok account @kampunginggrislccom can be considered an effective and engaging supporting medium for learning English vocabulary.